P282 Repetitive Transcranial Magnetic Stimulation (rTMS) improves catatonia features associated with Major Depressive Disorder (MDD): Case study. Issue 3 (March 2017) - Marei, A.; Rashed, H.
Abstract : Objective: To investigate the possible effect of rTMS in improving catatonic features associated with MDD. Case study: A 17 year old male patient with the diagnosis of MDD (DSM-IV 296.20) with catatonic features (motoric immobility, evidenced by stupor, negativism, mutism and posturing), was referred to our lab for assessment. The family stated that the patient stopping eating (losing 8 kg), drinking, talking plus sleep disturbances and assumption of certain postures for hours for a duration of 8 days. 2 protocols were done every session: (a) 30 pps, 100 pulse/train, 20 trains, 2 s inter train interval, intensity 10%, With total number of pulses 2000 each using stroke method over the scalp. followed by (b) 5 pps, 100 pulse/train, 20 trains, 20 s inter train interval, intensity 45% with total number of pulses 2, 000 over the LDPFC (F3) for 5 consecutive sessions for 2 weeks. TMS machine used was MagVenture Pro 30, with coil Type: 125. Results: drastic and rapid improvement after the first rTMS session as the patient was able to eat, drink few glasses of water, and sleep better but with no initial improvement on verbal and nonverbal communication. These improvements were sustained with enhancement of nonverbal and verbal communications by the 10th session. All through the course of treatment, we did not report any side effects from the rTMS. Conclusions: Catatonia is not an uncommon feature observed in psychiatric patients. Reports estimated that there are 90, 000 cases of catatonia occur each year in US hospitals. These reports also stated that the prevalence of catatonia ranges from 7.6% to 38% in psychiatric patients with more than half of the patients with an underlying bipolar affective disorder without clear demarcation of the type of bipolar affective disorder. Yet there were reports that about 20% of depressed patients met the criteria of catatonia. Benzodiazepines and Electro-compulsive Therapy (ECT) have been used to treatment of catatonia. In our current case, rTMS, which is a relatively safe and non-invasive technique with minimal cognitive distorting effects as compared to standard current therapies, improved catatonic features without side effects. Further researches are needed to confirm our results and test its long term effect.